2008
DOI: 10.1074/jbc.m707898200
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of RelB Requires Multidomain Interactions with p100/p52

Abstract: The NF-B family member RelB has many properties not shared by other family members such as restricted subunit association and lack of regulation by the classical IB proteins. We show that the protein level of RelB is significantly reduced in the absence of p100 and reduced even more when both p100 and p105 are absent. RelB stabilizes itself by directly interacting with p100, p105, and their processed products. However, RelB forms complexes with its partners using different interaction modes. Although the C-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 32 publications
5
48
0
Order By: Relevance
“…RelB associates with p100 through multiple protein-protein contacts. This multidomain interaction results in protein co-stabilization, as nfκb2 −/− cells showed reduced level of RelB protein and relb −/− cells have decreased amounts of p100 protein [69,70]. Counterintuitively, this interaction also inhibits p100 processing and RelB:p52 formation, suggesting that RelB:p52 dimer formation may occur after p100 processing, though it may involve alternate, transient interactions with p100.…”
Section: The Non-canonical Pathwaymentioning
confidence: 99%
“…RelB associates with p100 through multiple protein-protein contacts. This multidomain interaction results in protein co-stabilization, as nfκb2 −/− cells showed reduced level of RelB protein and relb −/− cells have decreased amounts of p100 protein [69,70]. Counterintuitively, this interaction also inhibits p100 processing and RelB:p52 formation, suggesting that RelB:p52 dimer formation may occur after p100 processing, though it may involve alternate, transient interactions with p100.…”
Section: The Non-canonical Pathwaymentioning
confidence: 99%
“…However, RelB must enable some processing of p100 to p52. This challenging dual tasking of RelB is solved elegantly: RelB uses its unique ability to form the p100-centric kappaBsome within which other NF-kB subunits may interact with p100 (32)(33)(34). Our study suggests that the generation of p52 occurs within the context of such a multiprotein complex.…”
Section: Discussionmentioning
confidence: 88%
“…Our work on p105:IκBγ revealed that p105 forms a dimer sequestering two NF-κB monomers although the precise mode of how p105 assembles with two NF-κB monomers is unknown. Interestingly, the C-terminal domain (CTD) of p105/IκBγ fails to bind RelB, although p50, the processed product of p105, interacts with RelB to form the p50: RelB heterodimer (26). We also showed that, like p105, p100 forms a large complex of unknown stoichiometry with NF-κB.…”
mentioning
confidence: 75%
“…RelB was subcloned into pEGFP-N1 vector (Clontech), and RelA was subcloned into pCMV HA vector. Transfection and fractionation by size-exclusion chromatography were done as previously described (26).…”
Section: Methodsmentioning
confidence: 99%